2018
DOI: 10.1111/jar.12466
|View full text |Cite
|
Sign up to set email alerts
|

Transition from school to adult services for young people with severe or profound intellectual disability: A systematic review utilizing framework synthesis

Abstract: Themes reflect the complex nature of the question what adulthood should look like for individuals with severe or profound intellectual disability. There is a lack of involvement of multiple stakeholders and young people themselves within studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…Tra le traiettorie pedagogiche che possono essere indirizzate ai caregiver che si preparano al percorso di distacco del "Dopo di Noi" menzioniamo un possibile lavoro parent training pedagogico per lo sviluppo di strategie di coping da attuare nel "Durante Noi". Prendere parte a specifiche forme di sostegno per condividere con altri genitori informazioni sui processi di transizione ai servizi dell'età adulta (Jacobs, MacMahon & Quayle, 2018) rappresenta, infatti, una delle possibili occasioni di anticipazione del progetto di vita del giovane adulto con disabilità. In tale direzione la promozione di atteggiamenti proattivi (Zafroni & Maggiolini, 2018), attraverso percorsi di consulenza genitoriale e/o di automutuo aiuto, contribuisce a pensarsi all'interno di un rapporto in divenire e in costante evoluzione.…”
Section: Conclusioniunclassified
“…Tra le traiettorie pedagogiche che possono essere indirizzate ai caregiver che si preparano al percorso di distacco del "Dopo di Noi" menzioniamo un possibile lavoro parent training pedagogico per lo sviluppo di strategie di coping da attuare nel "Durante Noi". Prendere parte a specifiche forme di sostegno per condividere con altri genitori informazioni sui processi di transizione ai servizi dell'età adulta (Jacobs, MacMahon & Quayle, 2018) rappresenta, infatti, una delle possibili occasioni di anticipazione del progetto di vita del giovane adulto con disabilità. In tale direzione la promozione di atteggiamenti proattivi (Zafroni & Maggiolini, 2018), attraverso percorsi di consulenza genitoriale e/o di automutuo aiuto, contribuisce a pensarsi all'interno di un rapporto in divenire e in costante evoluzione.…”
Section: Conclusioniunclassified
“…While these were considered current for the publication of the PhD, it has been suggested that systematic reviews should be ideally updated to one year before publication for interventions 72 . Given that this review used rigorous, transparent, systematic methods and more recently published reviews and guidance have not suggested newer uses of framework synthesis [73][74][75] , it is likely that the data underpinning these findings are representative of the method's current use 76 .…”
Section: Potential Limitationsmentioning
confidence: 99%
“…The transition from school to adult services has been described as the "black hole" (Doran, 2011) in the lives of individuals with intellectual disability and research has highlighted the need to improve practices in the UK (Stalker & Moscardini, 2012;Cox, 2017;Hudson, 2006). This study builds on a systematic review concerning this transition for young people with severe intellectual disability (Jacobs et al, 2018). The pathway to adulthood often differs for these young people (DeZonia, 2008;Simmons & Watson, 2014) and emerging adulthood can highlight the tension inherent in the gap between the individuals' abilities, possibilities and the acquisition of adult status (Jacobs & MacMahon, 2017;Pilnicket al, 2010Pilnicket al, , 2011Biswas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Within the transition to adult services, research shows that external factors have a significant influence on decision-making. Decisions are made by statutory services and families, and policies and resources available in local areas play crucial roles (Jacobs et al, 2018;Hardy et al, 2005;Lenehan, 2017). An ecological understanding to transitions has been shown promising in mapping facilitators and barriers across systems (Small et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation